Study of Some Immunological Markers of People with Parasitic Infestation and their Relationship to Colorectal Cancer (Medico Legal Update, 2021)
The aims of this study to find the link between each of the parasites(E. histolytic and Giardiasis) infectionand intestinal cancer, This study contain 4 groups :- Group (G1) People with cancer and diarrhea due tothe parasite (42) Group (G2) People with cancer and diarrhea without parasites (8) Group (G3) Peoplewith diarrhea and parasites (24) and Group (G4) Control (30), blood samples were collected from patientssuffering from diarrhea and parasite infection of both types, as well as cancer, Elisa kits were used in ourstudy the proteins (mucin 2, TFF3, CALP) level were measure by using Elisa kit that provided from theChina Origin Company Elabscience. The results of the current immunological study showed the level ofserum (mucin 2, TFF3, CALP) among the study groups, where the levels of mucin 2 values were (14305.00),(10595.00),(13145.00) and (9350.00)in group (1), and group (2), group (3) and group (4) respectively,and the level of serum values (TFF3)(43.15),(11.90),(29.65) and (8.60)with the same sequence of groupsabove, and the level of serum values CALP(16320.00),(11220.00),(15275.00) and(8690.00)with the samesequence of groups above as well. The results of the statistical analysis showed that there is a significantdifference between the study groups below the probability level (P